Chemically Modified Silk Proteins. Issue 7 (15th February 2018) - Chen, Jianming; Venkatesan, Harun; Hu, Jinlian
Abstract : Silks are of central importance as smart natural biomaterials and are attracting increasing attention for their biomimetic potential due to their sophisticated molecular structure, self‐assembly mechanism, impressive mechanical properties, biocompatibility, and biodegradability. The versatility of silk proteins (SP) allows the chemical modification of silk‐based materials with diverse morphologies under harsh conditions. The chemical modification of amino acids within SP enables the expanded generation of new biomaterials and the extension of their potential functional applications. The authors review the current chemical modification strategies and routes for the functionalization of SP. Abstract : This paper reviews recent advances in the development of chemically modified silk proteins for biomedical applications. Reactive groups in amino acids enable the chemical modification of silk proteins in various morphogies. Silk proteins are exemplified to show functionalization with peptides/enzymes, organic ligands, polymers, and minerals by the grafting reaction, coupling reaction, and amino acid modification.